Pre-professional internships and professional training of administration students at Ica - Perales, Jesús Vilca; García, Rosa Felicita Martínez; Espinoza Tucno, Leity Nicol; Jerí Hinostroza, Jackelyn Pamela; Nieto Fuentes, Eliana Paola; Ramos Ore, Karoline Zunet; Siguas Flores, Francis Alexander; Vasquez Gutiérrez, Adriana Lucia (Technium Education and Humanities, 2023)
Pre-professional internships in professional training serve to develop knowledge and practical skills and abilities in students that allow them to have new scenarios of their own professional career, put into practice the knowledge and skills acquired in their study stages. Currently, in Peru, according to Law, pre-professional internships carried out by students for a period equal to or greater than three months are recognized as work experience for performance in public and private institutions, benefiting thousands of interns nationwide, because jobs they ask for a certain amount of work experience; favoring them in a future job position. The purpose of the study was to determine, explain, and analyze the performance of pre-professional internships by students and the impact they have on their academic stage as well as on their professional life of university administration students.